STRATEGI PEMBELAJARAN DARING DI ERA COVID-19 UNTUK MENUMBUHKAN KEMAMPUAN BERFIKIR KREATIF MAHASISWA DI STKIP PESISIR SELATAN - Riri Lestari; Alexander Syam (STKIP Pesisir Selatan, 2020)
After the Covid-19 pandemic entered Indonesia which then in mid-March 2020 to reduce the number of Covid 19 sufferers, the provincial and local governments produced policies in the world of education, namely temporarily eliminating face-to-face learning and replaced with online learning at both the school and college levels, manifested in a system called an electronic university (e-university). Online learning makes it easy to provide information transfer in various situations and conditions, to foster creative thinking students still have to 1) try to focus on learning even though in the current pandemic conditions with a value of 0.894 then 2) manage study time regularly with a value of 0, 884, 3) Avoid all kinds of distractions that have the potential to interfere with the learning process with a value of 0.862 and 4) communication must be well established to avoid misunderstanding with a value of 0.850. Each priority will be carried out by lecturers and students working together to achieve the learning process.